Inclusive Education, Disability, and Interfaith Justice: Legal and Religious Barriers in Plural Indonesian Society - Lestari , Eta; Ani Purwanti; Ratna Herawati; Atmojo, Danang Puji; Saputra, Meidi (Contemporary Issues on Interfaith Law and Society, 2025)
Inclusive education is widely recognized as a fundamental human right; however, its realization for persons with disabilities remains uneven in plural societies such as Indonesia. This study examines inclusive education as an interfaith legal issue, arguing that the persistent failure to achieve substantive equality is not merely a problem of weak policy implementation but a consequence of normative dissonance among state law, religious norms, and social practices. Employing a juridical-empirical approach within a legal pluralism framework, the study draws on qualitative data from interviews, observations, and document analysis to explore how stigma and exclusion are socially and normatively produced. The findings reveal that disability stigma is reinforced through paternalistic religious interpretations, institutional routines in schools, and the lack of harmonization between Law No. 8 of 2016 on Persons with Disabilities and the National Education System Law. At the same time, religious values across faith traditions possess significant normative potential to function as modalities of inclusion when mobilized through interfaith engagement. This study contributes to socio-legal scholarship by reframing inclusive education as a contested normative space shaped by interfaith dynamics and legal pluralism, and by highlighting the necessity of legal reform alongside cross-religious collaboration to achieve substantive justice in education.